2007
DOI: 10.5194/angeo-25-2359-2007
|View full text |Cite
|
Sign up to set email alerts
|

On magnetospheric electron impact ionisation and dynamics in Titan's ram-side and polar ionosphere – a Cassini case study

Abstract: Abstract. We present data from the sixth Cassini flyby of Titan (T5), showing that the magnetosphere of Saturn strongly interacts with the moon's ionosphere and exo-ionosphere. A simple electron ionisation model provides a reasonable agreement with the altitude structure of the ionosphere. Furthermore, we suggest that the dense and cold exo-ionosphere (from the exobase at 1430 km and outward to several Titan radii from the surface) can be explained by magnetospheric forcing and other transport processes wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 33 publications
6
97
0
Order By: Relevance
“…Modelling activity by Agren et al (2007) showed that the night-time observation of a relatively dense ionosphere could be explained by the flux of magnetospheric electrons alone, although the observed intensity of these was higher than that needed to produce a good fit with RPWS LP ionosphere data.…”
Section: (B ) T5: Dark Ionospherementioning
confidence: 99%
“…Modelling activity by Agren et al (2007) showed that the night-time observation of a relatively dense ionosphere could be explained by the flux of magnetospheric electrons alone, although the observed intensity of these was higher than that needed to produce a good fit with RPWS LP ionosphere data.…”
Section: (B ) T5: Dark Ionospherementioning
confidence: 99%
“…The electron impact has been studied in Agren et al (2007), and re-analyzed in Cravens et al (2008Cravens et al ( , 2009, with an updated precipitation flux (used in this work). In order to fit the flux measurements at 1200 km with the model using a precipitation flux measured at 2730 km, the authors had to divide by 10 the input flux.…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…14 for several examples). Such a fact may significantly influence our understanding of the formation of nightside ions on Titan, which has been previously believed to be due to electron precipitation from Saturn's magnetosphere only (e.g., Cravens et al 2008aCravens et al , 2008bÅgren et al 2007). However, it appears from the Cassini observations that the transport of ions created at Titan's dayside may play an important role (Cui et al , 2010.…”
Section: Titan's Ionospheric Transport Processesmentioning
confidence: 98%
“…The energetic, hot electrons are from the external plasma in Saturn's magnetosphere passing Titan with a bulk speed of about 120 km/s. Their thermal velocity is much higher than the bulk speed (e.g., Coates et al 2007b;Ågren et al 2007;Cravens et al 2008a;. Both the bulk plasma flow and the high energy particle intensities in Saturn's magnetosphere, which the atmosphere of Titan experiences, varies with 2-3 orders of magnitude and is connected to the Saturn rotation period of about 10.7 hours (Bertucci et al 2009;Morooka et al 2009;Rymer et al 2009;Andrews et al 2010).…”
Section: Titan's Ionospheric Structurementioning
confidence: 98%